Polskie przedsiębiorstwa wobec wyzwań wynikających z procesu integracji europejskiej - Mazurek-Łopacińska, Krystyna; Sobocińska, Magdalena (Polish Companies in the Face of European Integration Challenges, 2007)
Poland's accession to the European Union in May of 2004 resulted in the creation of a new business environment. The article presents challenges that Polish companies have to face in the process of European integration. Improving Polish companies' competitiveness requires improving the staff qualifications and making market offer more attractive, which in many cases requires increased implementation of information technologies. Opportunities resulting from the process of European integration can be made greater use of by the programme of national branding, currently realized in Poland. Another challenge is increasing initiative in obtaining European funds which can help achieve objectives connected with improving the competitiveness of Polish companies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1170, s. 28-40